Investigation on colour and fastness properties of wool fabrics dyed with colours obtained from the flowers of the Papaver rhoeas L. (common poppy) - (:unkn) unknown (My University, 2012)
In this research, usability of the flowers of the Papaver rhoeas L. which has a wide expansion area throughout the world as natural dyes in dyeing the wool fibres was examined. Wool fabric was dyed through the conventional and ultrasonic methods with the dye extracted from the plant after it was mordanted with the common mordanting agents. L*a*b* values of the materials were measured and compared by using the CIE L*a*b* colour space system of the wool fabric samples. Moreover, washing and light fastness properties of the dyed materials were examined. It was observed that colour yield increased in dyeing made with natural dyestuff extracted from the Papaver rhoeas L. plant and through the dyeing method performed with environmentfriendly ultrasonic energy.
Keywords: Conventional method; Papaver rhoeas L.; Ultrasonic method; Vegetable dye; Wool